Experimental Investigation of GGBS Incorporated Concrete in the Aspect of Compression and Flexural Strength with M-Sand as Fine Aggregate - P.M. , Rameshwaram; M. , Mohana Ram; F. , Stella Mary (International Journal of Psychosocial Rehabilitation, 2020)
To make concrete an eco-friendly material and to reduce the carbon footprint on the environment, in this research work river sand is replaced fully with crushed sand (manufactured sand/M-sand) and ground granulated blast furnace slag (GGBS), which is replaced partially with cement. Ground granulated blast furnace slag is an industrial waste material that is obtained from the manufacturing industries of iron. By partially replacing the GGBS, the strength of concrete can be enhanced, and the durability property of the concrete can also be enhanced. With partial replacement of GGBS in Ordinary Portland Cement, the alkali-silica reaction can be alleviated. This is achieved by limiting the cement content of the concrete mix and thereby limiting the sum of alkali content in the concrete mix. GGBS is replaced in cement from 40% to 70% with a constant increment of 5%. By experiment, the study on workability, compression strength, and flexural strength of concrete is investigated.